NEWS PRODUCTION MANAGEMENT ”JABAR SABER HOAKS” IN OVERCOMING THE HOAX OUTBREAK ON SOCIAL MEDIA - Febrianti, Ranti; Nurhadi, Zikri Fachrul; Latifah, Hanny (Jurnal Spektrum Komunikasi, 2024)
This research emerged due to the increasing number of fake news on social media which has negative impacts such as misinformation and propaganda. This problem is getting worse because widespread access to social media is exacerbating the situation, even triggering social conflict. To overcome this, the West Java Diskominfo established Jabar Saber Hoaks on Instagram and websites to verify fake news and reduce its spread. The aim of this research is to understand how West Java Saber Hoaks manages news production in dealing with the spread of fake news on social media. This research uses a qualitative descriptive method with data collection techniques through in-depth interviews and observation. News production management is observed based on George R. Terry's management principles which include Planning, Organizing, Actuating, and Controlling or POAC. Research subjects included division heads, coordinators, dissemination heads, and West Java Saber Hoaks social media managers. The research results show that West Java Saber Hoax implements planning steps by setting priorities and analyzing hoax trends. Organizing is carried out by teams responsible for fact checking and social media. The clarification process is carried out by checking facts first, then distributing verified information through social media and websites. Control is carried out by monitoring the reach and response to clarifying news. In conclusion, Jabar Saber Hoaks has carried out careful planning, efficient organization, active implementation and careful control in fighting fake news on social media.